Elucidating the role of protein synthesis in hippocampus‐dependent memory consolidation across the day and night. (3rd February 2020) - Raven, Frank; Bolsius, Youri G.; van Renssen, Lara V.; Meijer, Elroy L.; van der Zee, Eddy A.; Meerlo, Peter; Havekes, Robbert
Abstract: It is widely acknowledged that de novo protein synthesis is crucial for the formation and consolidation of long‐term memories. While the basal activity of many signaling cascades that modulate protein synthesis fluctuates in a circadian fashion, it is unclear whether the temporal dynamics of protein synthesis‐dependent memory consolidation vary depending on the time of day. More specifically, it is unclear whether protein synthesis inhibition affects hippocampus‐dependent memory consolidation in rodents differentially across the day ( i.e., the inactive phase with an abundance of sleep) and night ( i.e., the active phase with little sleep). To address this question, male and female C57Bl6/J mice were trained in a contextual fear conditioning task at the beginning or the end of the light phase. Animals received a single systemic injection with the protein synthesis inhibitor anisomycin or vehicle directly, 4, 8 hr, or 11.5 hr following training, and memory was assessed after 24 hr. Here, we show that protein synthesis inhibition impaired the consolidation of context–fear memories selectively when the protein synthesis inhibitor was administered at the first three time points, irrespective of timing of training. Even though the basal activity of signaling pathways regulating de novo protein synthesis may fluctuate across the 24‐hr cycle, these results suggest that the temporal dynamics of protein synthesis‐dependent memory consolidation are similar for day‐time and night‐time learning. Abstract : In this study, we show that protein synthesis inhibition impairs the consolidation of context–fear memories when the anisomycin was administered directly, 4 or 8 hr after training, irrespective of timing of training. Even though the basal activity of signaling pathways regulating de novo protein synthesis may fluctuate across the 24‐hr cycle, these results indicate that the temporal dynamics of protein synthesis‐dependent memory consolidation are similar across the day and night.